The impact of disruptive powertrain technologies on energy consumption and carbon dioxide emissions from heavy-duty vehicles. (April 2020) - Smallbone, Andrew; Jia, Boru; Atkins, Penny; Roskilly, Anthony Paul
Highlights: The heavy duty (HD) vehicle and freight sector needs to be decarbonised. There are multiple technological pathways to achieving this. Technology roadmaps offer some insight into technology will develop. This paper uses these roadmaps to estimate how to decarbonise the HD sector. We explore the impact on size, weight, CO2 emissions and energy consumptions. Abstract: Minimising tailpipe emissions and the decarbonisation of transport in a cost effective way remains a major objective for policymakers and vehicle manufacturers. Current trends are rapidly evolving but appear to be moving towards solutions in which vehicles which are increasingly electrified. As a result we will see a greater linkage between the wider energy system and the transportation sector resulting in a more complex and mutual dependency. At the same time, major investments into technological innovation across both sectors are yielding rapid advancements into on-board energy storage and more compact/lightweight on-board electricity generators. In the absence of sufficient technical data on such technology, holistic evaluations of the future transportation sector and its energy sources have not considered the impact of a new generation of innovation in propulsion technologies. In this paper, the potential impact of a number of novel powertrain technologies are evaluated and presented. The analysis considers heavy duty vehicles with conventional reciprocating engines powered by diesel and hydrogen, hybrid and battery electric vehicles and vehicles powered by hydrogen fuel cells, and free-piston engine generators (FPEGs). The benefits are compared for each technology to meet the expectations of representative medium and heavy-duty vehicle drivers. Analysis is presented in terms of vehicle type, vehicle duty cycle, fuel economy, greenhouse gas (GHG) emissions, impact on the vehicle etc. . The work shows that the underpinning energy vector and its primary energy source are the most significant factor for reducing primary energy consumption and net CO2 emissions. Indeed, while an HGV with a BEV powertrain offers no direct tailpipe emissions, it produces significantly worse lifecycle CO2 emissions than a conventional diesel powertrain. Even with a de-carbonised electricity system (100 g CO2 /kWh), CO2 emissions are similar to a conventional Diesel fuelled HGV. For the HGV sector, range is key to operator acceptability of new powertrain technologies. This analysis has shown that cumulative benefits of improved electrical powertrains, on-board storage, efficiency improvements and vehicle design in 2025 and 2035 mean that hydrogen and electric fuelled vehicles can be competitive on gravimetric and volumetric density. Overall, the work demonstrates that presently there is no common powertrain solution appropriate for all vehicle types but how subtle improvements at a vehicle component level can have significant impact on the design choices for the wider energy system.